Neonatal haemolytic disease with co-existing Anti-D and Anti-C antibodies: an unusual experience - Durrani, Hafiza Mehreen; Zaman, Zubia; Mansoor Raza, Imran; Jamali, Munira; Saleem, Ayesha; Muzammil Ejaz, Shabana (Journal of the Pakistan Medical Association, 2022)
Neonatal haemolytic disease in the new-born remains of prime importance for paediatricians due to high perinatal morbidity and mortality rates. The Rh antigen family comprises several different antigens, out of which, D antigen incompatibility is well known for causing severe haemolytic disease in the foetus. Although the current literature shows anomalous cases where coexisting non-D-Rh and D-Rh antigens are the causative agents, there is very little information regarding post-natal outcomes in neonates bearing two different incompatibilities simultaneously. Herein, we discuss an unusual case of anti-D as well as anti-C antibodies (non-D-Rh) in a male neonate born to a Rh-negative mother, who developed jaundice and haemolysis in post-natal life. The neonate underwent exchange transfusion and photo therapy due to raised serum bilirubin levels, supplemented with repeated blood transfusions, intravenous immunoglobulin therapy, and immunosuppressive therapy. --Continue